Evaluation of Antioxidant and Antiproliferative Properties of Cornus mas L. Fruit Juice - Angeliki Tiptiri-Kourpeti; Eleni Fitsiou; Katerina Spyridopoulou; Stavros Vasileiadis; Christos Iliopoulos; Alex Galanis; Stavroula Vekiari; Aglaia Pappa; Katerina Chlichlia (MDPI AG, 2019)
Cornus mas L. (Cornelian cherry) is a flowering plant indigenous to Europe and parts of Asia, mostly studied for the antimicrobial activity of its juice. In this report, we investigated the composition and the in vitro antioxidant capacity of Cornus mas L. fruit juice from Greece, as well as its antiproliferative properties in vitro and in vivo. The fruits showed a high content of citric, malic, and succinic acid, in contrast to their juice, which had a low concentration of organic acids. The juice demonstrated significant antioxidant activity against the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) and modest antiproliferative potential against four human cancer cells lines and one murine: mammary adenocarcinoma MCF-7, hepatocellular carcinoma HepG2 and colon adenocarcinomas Caco2, HT-29, as well as murine colon carcinoma CT26. Cell viability was reduced by 40−50% following incubation of the cells with the highest concentration of the juice. Although Cornelian cherry juice exhibited in vitro growth inhibitory effects against colon carcinoma cells, no tumor growth inhibition was observed in an in vivo experimental colon carcinoma model in mice following prophylactic oral administration of a daily dose of 100 μL juice for a period of 10 days. Thus, our findings raise interesting questions for further research on Cornus mas L. fruit juice, and in parallel, the strong antioxidant potential implies that the plant could be further explored and exploited for its protective effect against oxidative damage.